2012
DOI: 10.5543/tkda.2012.01826
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma asymmetric dimethylarginine level and autonomic dysfunction in diabetic patients

Abstract: Our findings show that plasma ADMA levels are increased and HRV is reduced in diabetic patients, indicating that these patients have both endothelial dysfunction and autonomic dysfunction, but plasma ADMA levels cannot be used to evaluate autonomic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Five studies assessed the influence of high blood pressure on HRV in T2DM compared with healthy controls [49,50,54,55,58]. Other studies compared HRV between T2DM patients and controls based on blood catecholamine levels [44], circadian autonomic rhythm in insulinoresistant subjects [45], in cases of bowel preparation [63], metabolic syndrome [47], circadian rhythm in relation to blood adiponectin [62], or dimethylarginine levels [61], hypoglycaemic episodes [59], in acromegalic patients [53], and inhalation of ultrafine particles [57].…”
Section: Objectives Of Included Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies assessed the influence of high blood pressure on HRV in T2DM compared with healthy controls [49,50,54,55,58]. Other studies compared HRV between T2DM patients and controls based on blood catecholamine levels [44], circadian autonomic rhythm in insulinoresistant subjects [45], in cases of bowel preparation [63], metabolic syndrome [47], circadian rhythm in relation to blood adiponectin [62], or dimethylarginine levels [61], hypoglycaemic episodes [59], in acromegalic patients [53], and inhalation of ultrafine particles [57].…”
Section: Objectives Of Included Articlesmentioning
confidence: 99%
“…In each individual study, exclusion criteria were the same as for T2DM, i.e. pregnancy [43,62], neurological disease [43], BMI over 25 kg/m 2 [42,44,45] or 35 kg/m 2 [58,62], chronic heart [42,44,45,[50][51][52]57,58,[60][61][62][63], liver [56,60,63], or renal [42,42,45,56,58,[60][61][62][63] failure, thyroid disorder [50,52], or treatment that can influence HRV parameters [44][45][46]52,54,[57][58][59][60]. Controls had high blood pressure in five studies [49,56,58,60,62], and were on dialysis in three studies [43,…”
Section: Inclusions and Exclusions Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The abnormal glucose metabolism due to DM may induce cardiomyopathy and lead to changes on the echocardiography (ECG). In previous research, the effects of DM on ECG were concentrated in heart rate variability, [1][2][3][4][5][6] RR interval, 6 T-wave alternans, 7 QTc interval, [8][9][10] and ST segment, 11 which are predictive of cardiac mortality and diagnosis of silent myocardial infarction in DM. Recent reports showed that the maximal magnitude of frontal QRS-T angle (FQRSTA) was significantly associated with the prognosis of elderly patients, 12 myocardial infarction, [13][14][15][16][17] heart failure, 17 and chronic dialysis.…”
mentioning
confidence: 99%